Identifying Subaltern Group(S) or Individual(S) in the Works of Mulk Raj Anand: Exploring the Representation of Underprivileged Groups in Mulk Raj Anand's Works (Journal of Advances and Scholarly Researches in Allied Education, 2022)
In his works, Dr. Mulk Raj Anand accurately and sensitively depicts the subaltern class of Indiaat the time. Anand rose to prominence as an advocate for underrepresented populations. His writingsinclude books, short stories, and cultural essays. The writings of Anand, the first Indian author to write inEnglish, depict the oppressed Indian people's actual struggles. Mulk Raj Anand is a writer who ispassionate about social justice and has written a number of books on it. The growth of Indian writing inEnglish has been strongly affected by the works of renowned author Mulk Raj Anand.